2018
DOI: 10.1039/c8re00087e
|View full text |Cite
|
Sign up to set email alerts
|

Integrated plug flow synthesis and crystallisation of pyrazinamide

Abstract: Pure pyrazinamide has been produced in a coupled flow synthesis and crystallisation in high yield, pure polymorphic form (γ) and narrow particle size distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Various types of crystallization have been demonstrated in slug flow [10], including reactive precipitation [27,[41][42][43][44][45][46], cooling crystallization [3,39,40,47,48], and anti-solvent crystallization [49,50]. Several compounds (e.g., L asparagine monohydrate [3], acetylsalicylic acid [39], and succinic acid [27]) were crystallized into uniform crystals of up to a few hundred microns in millifluidic slugs.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of crystallization have been demonstrated in slug flow [10], including reactive precipitation [27,[41][42][43][44][45][46], cooling crystallization [3,39,40,47,48], and anti-solvent crystallization [49,50]. Several compounds (e.g., L asparagine monohydrate [3], acetylsalicylic acid [39], and succinic acid [27]) were crystallized into uniform crystals of up to a few hundred microns in millifluidic slugs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications of crystallisations in the KRAIC, 21,27 we noted the production of unexpected polymorphs from aqueous-based crystallisation. In the case of pyrazinamide (PYZ), pure γ-PYZ was produced unless blockages were encountered during crystallisation, in which case the expected α-PYZ was also obtained.…”
Section: Crystallisation Of Succinic Acid In the Kraic-rmentioning
confidence: 67%
“…In the case of pyrazinamide (PYZ), pure γ-PYZ was produced unless blockages were encountered during crystallisation, in which case the expected α-PYZ was also obtained. 27 In SA crystallisation, small impurities of α-SA were found present in the expected β-SA product. 21 We have hypothesised that the absence of a liquidsolid boundary (due to the tri-segmented flow environment) during nucleation has resulted in this unusual polymorphism, although recent results from Simone et al show that a small amount of α-SA can form from solution-based crystallisation within FEP tubing (both hydrophilic and hydrophobic) without a carrier fluid barrier.…”
Section: Crystallisation Of Succinic Acid In the Kraic-rmentioning
confidence: 96%
“…Scott and co-workers designed and demonstrated a system which allowed inline crystallisation in a truly continuous manner. 172 The approach involved the use of a tri-segmented tubular crystallizer (KRAIC) in the form of three coil reactors (1/8″ ID FEP tubing, 15 m) in which the reaction mixture is segmented with air and an immiscible carrier solvent This journal is © The Royal Society of Chemistry 2021 allowing in-line crystallization. Notably the authors found it necessary to insert a section of jacketed tubing between the segmentor and the KRAIC which was cooled to 10°C to ensure the rapid formation of large numbers of nuclei.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%